Estranhamento (entfremdung) no trabalho: o Unibanco na virada dos anos 90 - Rocha, Danielle Franco da (2006)
The objective of this study is to investigate alienation and strangeness (Entfrendung) in banking work, taking as an specific case study, the analysis of the UNIBANCO employees experience in the turn of the 1990s. That is a moment of great changes in the labour world that reinforces the ways of obtaining non-paid work and the consequent imposition of value in the productive world. The specificity of this kind of work and its function in the global capital system is to transform the money commodity, which is a capacity separated from men, in interest producing capital. This process occurs and takes the appearance of money producing more money . In this context, the globalization of capital helps the huge increase in capital flow to be incorporated and done by the bank employees, which increases the contradiction to the daily bank work routine and its relationship with the social reproduction of life. Still in this sense, this study shows the role of credit in the capitalist accumulation process and its impacts in Brazilian economy. In this sense, the labour banking world, as a true agent, entails the whole system of human life production in which labour becomes stranged in its alienated form